OLIVINE-CHROMSPINEL OXYTHERMOBAROMETRY OF ULTRAMAFIC ROCKS OF THE ǏOKO-DOVYREN LAYERED MASSIF - Pushkarev E.V.; Votyakov S.L.; Chashchukhin I.S.; Kislov E.V. (My University, 2004)
Redox-condition of stratified ultramafite infusions is estimated by the modern methods of oxythermobarometry. Olivine-chromespinel equilibrium of ultramafites of the Ioko-Dovyrensk's stratified massive is studied. Temperature and fugacity of oxygen are evaluated on this basis at the instant of ending the exchange subsolidus reactions. Attempt is made to define the variations of fluid regime of rocks formation upon their interaction with the metasedimentary carbonate rocks.